The rhetoric and practice of business research collaboration among High North universities - Dybtsyna, Elena; Hersinger, Anders; Middleton, Alexandra (The Arctic Centre, University of Lapland, 2019)
International research collaboration and business development in the High North have become hot topics at the governmental policy level in many countries. However, despite prior research on cooperation between Nordic universities, there is a dearth of research specifically addressing the practice of High North research collaboration in business studies. We ask the following research question: how are the prospects for business research collaboration among High North universities portrayed in national policy documents and to what extent is business research in the High North collaborative in practice? We address this question by analyses and comparisons of publicly available governmental Arctic strategies and bibliographic data on joint publications between researchers from High North universities in Finland, Norway, and Sweden. The empirical results reveal diverging yet far-reaching national aspirations at the policy level which do not match the rather modest research collaboration in practice evidenced by our bibliographic data. Our conclusions suggest that the rhetoric of High North business research collaboration and the practice of actual collaboration among High North universities are decoupled from each other. We theorize about explanatory circumstances behind decoupling in the area of research collaboration and provide suggestions for further research. publishedVersion